PERBEDAAN PENGARUH LATIHAN SQUAT JUMP DENGAN STANDING JUMPTERHADAP TINGGI LONCATAN PEMAIN BOLAVOLI PUTRA FIP UNIVERSITAS NEGERI MALANG - Wahyu Fajar Arifin; Saichudin Saichudin; Mahmud Yunus (Universitas Negeri Malang, 2017)
ABSTRACT: Men volleyball players of FIP State University of Malang less understanding in the application of theory and methods to form a model of exercise. The purpose of this study was to determine the effect of squat jump and standing jump exercises as a stepping up and more effective training between both. The design of this study used pretest posttest design with group selection using ordinal pairing matching. The instrument used is a vertical jump test. Based on result of data analysis, that is t count equal to 11,784> t table = 1,795 and for standing jump exercise also have influence that is t count equal to 6,862> t table = 1,795. Of both average results the squat jump exercise is better than standing jump exercise.Keyword: squat jump and standing jump exercises, jump height, volleyball